OPTIMIZATION OF CROSCARMELLOSE AND SODIUM STARCH GLYCOLATE ON ORALLY DISINTEGRATING METOCLOPRAMIDE HCL TABLETS - Endang Diyah Ikasari; Intan Martha Cahyani; Deby Melinda Collusy (Universitas Muhammadiyah Magelang, 2022)
Dosage form of metoclopramide HCl which has high solubility but low permeability is Orally Disintegrating Tablet (ODT), because can decrease first-pass-effect metabolism so that its bioavailability and effectiveness increase. Superdisintegrant is an excipient that has a major role in the formulation of ODT. The combination of croscarmellose and Sodium Starch Glycolate (SSG) can accelerate tablet disintegration time so that the resulting ODT is suitable for its intended use. The purpose of this study was to determine the effect of each and the interaction of the use of croscarmellose and SSG on the physical characteristics of ODT metoclopramide HCl, and to get the optimum formula of ODT metoclopramide HCl. Tablets were prepared by direct compression method. Optimization process by using simplex lattice design (design expert 10.0.1.R program) with eight formulas, including FI (5.25%A:1.75%B), FII (0%A:7%B), FIII (7%A:0%B), FIV (1,75%A:5,25%B), FV (7%A:0%B), FVI (3.5%A:3.5%B), FVII (3.5%A:3.5%B) and FVIII (0%A:7%B). Component A is the concentration of croscarmellose and component B is the concentration of SSG. Based on SLD equation could be seen the single-use croscarmellose and SSG components be increased flowability, hardness, moisture content, friability, water ratio absorption, weight uniformity, uniformity of content, accelerate disintegration time, wetting time, and dissolution. Interaction of the two components was increased flowability, moisture content, water ratio absorption and dissolution, decreased hardness, friability, uniformity of content, weight uniformity, accelerate disintegration time, and wetting time. The optimum formula of ODT metoclopramide HCl with proportion 5.145% croscarmellose and 1.855% SSG. Based on the one sample t-test between theoretical results and the experimental results could be seen that there were no significant differences between them